2020
DOI: 10.32598/jams.23.1.5710.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salivary and Gingival Crevicular Fluid Periostin Levels in Chronic Periodontitis Patients and Healthy Subjects

Abstract: Background and Aim Periostin acts as necessary protein in tissue development and has a key role in tooth-supporting tissues such as periodontal ligament. The effect of inflammation on reducing periostin level has been shown in some studies. The aim of this study was to compare the salivary and Gingival Crevicular Fluid (GCF) periostin levels in patients with chronic periodontitis and healthy peers. Methods & Materials In this matched case-control study, 106 participants (53 patients with chronic periodontitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These findings are consistent with other studies conducted in Iran and Korea (44,54). However, the findings of this study are not consistent with some other studies (38,55,56).…”
Section: Discussionsupporting
confidence: 66%
“…These findings are consistent with other studies conducted in Iran and Korea (44,54). However, the findings of this study are not consistent with some other studies (38,55,56).…”
Section: Discussionsupporting
confidence: 66%
“…A higher score indicates more job burnout. The validity of the job burnout questionnaire has been confirmed by Momeni et al [44]. Also, Ghaniyoun et al ( 2016) have confirmed the face and content validity of this questionnaire [45].…”
Section: Study Instrumentsmentioning
confidence: 74%
“…In essence, as the levels of job burnout escalate, a tendency for rehabilitation therapists to harbor increasingly negative attitudes towards individuals with disabilities becomes apparent. Job burnout encompasses a multifaceted state marked by physical, emotional, and cognitive fatigue, precipitated by protracted exposure to demanding work conditions, coupled with interprofessional conflicts and a waning commitment to both the work and its recipients [22]. Within the confines of this syndrome, individuals grapple with reduced vigor, diminished competence, and a growing reluctance to engage in work-related tasks.…”
Section: Discussionmentioning
confidence: 99%